Celiac Disease among Adults and Children in AL-Anbar Province West of Iraq: a Comparative Cross-Sectional Study - Yasin. Hamad Majeed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: gluten-sensitive Enteropathy is a public non-communicable, immune-associated disease whichis activated by wheat (gluten) ingesting that occur in hereditarily susceptible individuals in initial childhood& elderly individuals with varied presentations whereas several studies have shown CD are predominantin adults. The purpose of this study was to compare the clinical presentation, serological, endoscopic, andhistopathological features in adults and children with celiac disease at Al-Anbar province, west of Iraq. Atotal of 170 consecutive newly confirmed CD patients in AL-Ramadi teaching hospital, GastroenterologyClinic during a period between August 2017 & Jun 2020 had been involved in comparative cross-sectionaldesign research. Patients were divided into two groups: adults and children and each of them was alsodivided into two groups- classical and non-classical celiac disease based upon the clinical presentation.Clinical presentation, endoscopic findings were recorded.in all cases gastrointestinal endoscopy & duodenalbiopsy with Anti -TTG lgA had been determined & tested for the CD diagnosis. Histopathology results hadbeen divided using modified Marsh taxonomy. Results had been examined through a suitable statisticaltest. Of 170 CD patients that include 97 (57.1%) adults CD and 73(42.9) children. Classical symptomswere predominant among 85.56% of adults while non-classical symptoms were more common among45.2% of children. Bloating with abdominal pain and anemia were predominant among adults and childrenrespectively. No significant differences in the Levels of anti –tTG among each of adults and a pediatricgroup of CD patients (P-Value 0.072). The most common endoscopic finding was scalloping 60.3%, 40.2%)among children and adults respectively. Marsh grade G3A were predominant among adults [83 (89.2%)]versus [67 (95.7%)] among children of CD patients with anti-tTG lgA U/ml 10+1 and more levels.No statistical difference regarding marsh grade G3 frequency among adults and children CD patients (p0.191).